Functional Capacity of Oldest Old Living in a Long-stay Institution in Rio De Janeiro, Brazil - Freitas, Jeter Pereira de; Costa, Susana Ortiz; Dias, Fabiano Moura; Mainenti, Míriam Raquel Meira; Adriana da Costa Rocha Pinto; Vigário, Patrícia dos Santos (Journal of Physical Therapy Science, 2014)
[Purpose] A significant increase in the number of oldest old has occurred worldwide. The aim of this study was to characterize the functional capacity of the oldest old residents in a long-stay institution in Rio de Janeiro, Brazil. [Subjects and Methods] All participants were evaluated according to the following metrics: anthropometry, body composition (bioelectrical impedance), handgrip strength, balance (Berg scale and stabilometry), ankle mobility (electrogoniometry), physical capacity (six-minute walk test), quality of life (WHOQOL-OLD), and dietary habits (questionnaire). [Results] Twenty elderly subjects with a mean age of 85.75 ± 5.22 years and a mean fat percentage of 39.02 ± 5.49% participated in the study. The group at risk of falls (n = 8) had a lower handgrip strength and walked a shorter distance over the course of six minutes compared with the group not at risk of falls. The obese group (n = 15) had higher values for stabilometric variables than the nonobese group. There was a positive and significant correlation between ankle joint mobility and physical capacity (r = 0.47). [Conclusion] High values for obesity and low values for handgrip strength and physical capacity were associated with worse body balance. Low values for ankle mobility were also associated with worse physical capacity in this population.